Requirements of Enjoyable Mobile Learning Applications for Deaf Children (Journal of Information and Communication Technology, 2024)
In the domain of mobile learning applications for deaf children, many studies are more concerned with the development of mobile learning applications for deaf children than with determining what makes them enjoyable for this group of children. Some of these learning applications do not meet the needs of deaf children for learning since the requirements were not collected from the actual deaf children. As a result, many deaf learning applications are still not gaining much popularity among people who are deaf or hard of hearing due to the application due to the applications’ inability to meet their expectations and needs. Hence, this paper aims to identify the requirements for designing an enjoyable mobile learning application for deaf children. In achieving this goal, it is essential to identify the requirements of deaf children on mobile learning applications from their own everyday experience and support these identified needs with requirements gathered from their parents and teachers and literature. Three methods were conducted for this study to identify and synthesise these requirements: (1) Fun Sorter data collection method was conducted among the deaf children, whose ages are between 7 and 12 years old; (2) an interview involving teachers and parents of deaf children; and (3) a literature review on deaf children’s learning. The identified requirements were verified through a focused group attended by eight mobile learning developers. The finding identified six requirements: multimedia elements, games, easy-to-use, simple tasks, guidance,and alerting. These requirements serve as crucial guidelines for mobile app developers, enabling the creation of enjoyable learningapplications designed specifically for deaf children. Furthermore, these requirements can potentially improve the learning journey ofdeaf children, offering them valuable benefits and enhancing their educational experiences.